The Effect of Firm Size and Working Capital Turnover on Firm Value Mediated by Profitability and Intellectual Capital as Moderating Variable in Food and Beverage Companies Listed on IDX in 2017-2021 - Fide Theresia; Haryetti Haryetti; Dian Pratiwi (IJEBA (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS), 2023)
This research aims to determine the effect of firm size and working capital turnover on firm value mediated by profitability and intellectual capital as moderating variable in food and beverage companies listed on the Indonesia Stock Exchange in 2017-2021. The population in this research are 37 food and beverage companies listed on the Indonesia Stock Exchange in2017-2021. This research used purposive sampling as the sampling technique, so that 21 companies were obtained as the research samples. The data analysis used in this research is moderated regression analysis and sobel test with Statistical Program for Social Science (SPSS) 26. The results showed that firm size had no effect on firm value, working capital turnover had no effect on firm value, profitability had a positive effect on firm value, firm size had a positive effect on profitability, working capital turnover had a positive effect on profitability, firm size had an indirect effect on firm value through profitability, working capital turnover had an indirect effect on firm value through profitability, intellectual capital moderates the effect of firm size on profitability, intellectual capital moderates the effect of working capital turnover on profitability, intellectual capital do not moderate the effect of firm size on firm value, intellectual capital do not moderate the effect of working capital turnover on firm value, and intellectual capital do not moderate the effect of profitability on firm value.